2023
DOI: 10.1099/mic.0.001307
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite efflux pumps of the RND superfamily: what did we learn from computational studies?

Abstract: Bacterial resistance to antibiotics has been long recognized as a priority to address for human health. Among all micro-organisms, the so-called multi-drug resistant (MDR) bacteria, which are resistant to most, if not all drugs in our current arsenal, are particularly worrisome. The World Health Organization has prioritized the ESKAPE ( Enterococcus faecium , Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 187 publications
(455 reference statements)
0
8
0
Order By: Relevance
“…Recent additions to the literature on peptidoglycan model development for both Gram-positive and Gram-negative strains as well as attempts to model the complex landscape of the periplasm have been addressed. We have not discussed literature concerning the transmembrane protein machinery involved in lipid transport and folding as well as efflux pump action, and recent reviews , cover the literature in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Recent additions to the literature on peptidoglycan model development for both Gram-positive and Gram-negative strains as well as attempts to model the complex landscape of the periplasm have been addressed. We have not discussed literature concerning the transmembrane protein machinery involved in lipid transport and folding as well as efflux pump action, and recent reviews , cover the literature in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Computational studies have been widely used to investigate efflux machinery (Athar et al, 2023 ). Early simulations did not focus explicitly on the proton relay network, instead utilising postulated protonation states (Seeger et al, 2008 ).…”
Section: Structural Data and Early Simulation Studiesmentioning
confidence: 99%
“…Further simulations by the same group displayed flexibility in the porter domain, with opening and closing of the periplasmic cleft (Fischer and Kandt, 2013 ). For an extensive discussion of RND simulation studies, we direct the reader to a recent review (Athar et al, 2023 ). Here we turn our attention only to simulation studies where the protonation states of the proton relay network residues have been a primary focus.…”
Section: Structural Data and Early Simulation Studiesmentioning
confidence: 99%
“…Crystallized protein domains of RND efflux systems in the presence and absence of substrates or inhibitors provided a wealth of information on assembly and function [see ( Alav et al., 2021 ; Athar et al., 2023 )]. Analyses of the crystal structures of multiple RND transporter homologues revealed that RND pump proteins are structurally conserved; they all include multiple substrate entry portals and several substrate binding sites which mediate uptake of substrates from the periplasm and from within the cytoplasmic membrane.…”
Section: Rnd Efflux Systems Are Ubiquitous Transporters Among Gammapr...mentioning
confidence: 99%